2019
DOI: 10.1111/ijfs.14435
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of oil uptake during deep frying and applications of predrying and hydrocolloids in reducing fat content of chips

Abstract: Summary Deep frying resulting in high‐fat content is extensively used in the food industries and domestic households, and becoming an integral diet globally. The physical and chemical changes and oil uptake contributes to the unique taste and texture of fried food. Consumption of food high in fat is a health concern due to the increasing rate of obesity and cardiovascular diseases. Consumer awareness has led food industries to aim at fat reduction while maintaining the organoleptic properties of fried foods. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 70 publications
2
35
0
1
Order By: Relevance
“…There was a ready market for sweetpotato as it was comparable to yam in terms of production and utilisation, and accessible to the poor when yam was unaffordable. Yellow‐fleshed varieties with high dry matter content predominated due to attractive appearance and low oil consumption during frying, which is related to low moisture or high dry matter content (Lumanlan et al ., 2020a).…”
Section: Utilisation and Demand For Sweetpotato In West Africamentioning
confidence: 99%
“…There was a ready market for sweetpotato as it was comparable to yam in terms of production and utilisation, and accessible to the poor when yam was unaffordable. Yellow‐fleshed varieties with high dry matter content predominated due to attractive appearance and low oil consumption during frying, which is related to low moisture or high dry matter content (Lumanlan et al ., 2020a).…”
Section: Utilisation and Demand For Sweetpotato In West Africamentioning
confidence: 99%
“…There is growing interest in methods that could minimize oil uptake and reduce the fat content of fried foods. Hydrocolloids have been applied indiscriminately as a food coating or incorporated into chip formulation and have shown promising fat reductions and moisture retention during frying [14]. Hydrocolloids are natural compounds, such as polysaccharides and proteins, which have some hydrophilic groups.…”
Section: Introductionmentioning
confidence: 99%
“…Fried foods commonly high in fat content contributes to the distinctive flavour and better texture profile that can only be achieved by deep‐frying (Kurek et al ., 2017). The development of the porous crust where most oil adheres is associated with improving the crispy texture of fried food (Lumanlan et al ., 2020). These favourable characteristics have corresponded to their popularity and higher sales all over the world.…”
Section: Introductionmentioning
confidence: 99%
“…However, paper published by Lumanlan et al . (2020) indicated that reducing the moisture content and the addition of food gums before deep‐frying could lead to fat reduction and improve food quality, such as crispiness on some fried foods.…”
Section: Introductionmentioning
confidence: 99%